KNOWLEDGE AND PERCEPTION OF HAND HYGIENE AMONG HEALTH CARE WORKERS OF A TERTIARY CARE MILITARY HOSPITAL: A DESCRIPTIVE STUDY: Hand Hygiene Among Health Care Workers - Iqbal, Mahmood; Zaman, Muhammad; Azam, Naila (Pakistan Armed Forces Medical Journal, 2018)
Objective: To determine the knowledge and perception of doctors and paramedical staff about hand hygiene of atertiary care military hospital.Study Design: Cross sectional descriptive study.Place and Duration of Study: Study was conducted at tertiary care military hospital, from Aug 2016 to Jan 2017.Material and Methods: The sample size 196 was calculated using World Health Organization sample sizecalculator. Permission from administrative authorities was taken. Purposive sampling technique was used.World Health Organization’s knowledge and perception structured self-administered questionnaire was usedwith minor amendments for the data collection. The percentage’s in knowledge and perception domain of >75%determined good, 50-75% fair and